A Bizarre Abdominal Cystic Lesion - Zucchini, Giorgia; Pezzilli, Raffaele; Ricci, Claudio; Casadei, Riccardo; Santini, Donatella; Calculli, Lucia; Corinaldesi, Roberto (JOP. Journal of the Pancreas, 2010)
In spite of careful intraoperative precautions and gauze counts, mistakes can still occur during surgery. In the case reported, a retained gauze leaved during a surgical approach for removing a solid-cystic papillary tumor localized in the pancreatic tail, caused both persistent abdominal discomfort and the presence of an abdominal cystic lesion at imaging techniques. When a previous operative history is present, a foreign body should be taken into account in the differential diagnosis of a patient with an intra-abdominal cystic mass. Finally, radio-opaque marker should be routinely used by surgeons in order to reach a correct diagnosis in operated patients having retained gauze. Image: The cyst was then opened ...